Extended π-conjugated ruthenium zinc–porphyrin complexes with enhanced nonlinear-optical properties1. Issue 14 (18th February 2015) - de Torres, Miriam; Semin, Sergey; Razdolski, Ilya; Xu, Jialiang; Elemans, Johannes A. A. W.; Rasing, Theo; Rowan, Alan E.; Nolte, Roeland J. M.
<x xml:space="preserve">Abstract</x> Zinc porphyrin dimers and trimers, in which the porphyrins are connected via a ruthenium metal core, exhibit large third-order nonlinear optical absorption coefficients and refractive indices.